An Innovative Fuzzy Rule Based Control Analysis of Advanced Unified Power Flow Controller - Srivastava, S. K. (New Approaches in Engineering Research Vol. 1, 2021)
Due to rapidly development of high power semiconductor devices with fast control features have made possible to control the power flow more efficiently and effectively. The Flexible AC Transmission Systems (FACTS) in this category introduces several innovative operating control devices. One of the recent device is Advanced Unified Power Flow Controller (AUPFC) or multi-converter UPFC or Generalized-UPFC, which can control bus voltage and power flows, both real and reactive, of more than one line or even a sub-network. This chapter presents an innovative real time based approach for analysis of Advanced Unified Power Flow Controller. Based on the analysis, a new fuzzy logic rules based controller has been proposed which improves the system performance. The controller rules are structured depending upon the relationship between series inserted voltages in multi-line and the desired changes of real/reactive power flows in the power system. The effects of different controllers along with parameters of series transformers and transmission lines have been investigated through developed control block models in SIMULINK. The effectiveness of the proposed scheme is demonstrated by a case study.